The Impact of the Knowledge Management Dimension on the Performance of MSMEs - fadli Anugrah; Deky Hamdani; Ayu Esteka Sari (Citakonsultindo, 2024)
This article discusses the importance of Knowledge Management Dimension on the Performance of MSMEs. The data used in this study are primary data through interviews and a list of questions with a questionnaire. Analysis of the data in this study using a structural equation model with the analytical tool used is using AMOS. The results showed that the coefficient of determination of Knowledge management influence could explain by the Knowledge Sharing, Knowledge Creation and Knowledge Implementing about 88,6%. The coefficient of determination for the magnitude of Organizational performance influence, which can be explained by the organization's variable dimensions of organizational culture, organizational structure, training, and knowledge sha Knowledge Sharing, Knowledge Creation, Knowledge Implementing and Knowledge management aboout 6,9%. From testing the hypothesis that Knowledge Sharing, Knowledge Creation and Knowledge Implementing positively and significantly affects Knowledge management. But on testing the hypothesis that Knowledge Sharing, Knowledge Implementing and Knowledge management also positively and significantly affects Organizational performance, While knowledge creation negatively and not significantly affects Organizational performance.